2018
DOI: 10.1029/2018jc013999
|View full text |Cite
|
Sign up to set email alerts
|

First Direct Estimates of Volume and Water Mass Transports Across the Reykjanes Ridge

Abstract: The Reykjanes Ridge is a major topographic feature located south of Iceland in the North Atlantic Ocean that strongly influences the subpolar gyre circulation. Based on velocity and hydrographic measurements carried out along the crest of the Reykjanes Ridge from the Icelandic continental shelf to 50°N during the RREX cruise in June-July 2015, we derived the first direct estimates of volume and water mass transports over the Reykjanes Ridge. North of 53.15°N, circulation was mainly westward; south of this lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 48 publications
5
41
1
Order By: Relevance
“…At 1000-m depth, Argo floats reveal a continuous current following the Eastern RR flank until reaching the CGFZ, with some of the flow crossing the ridge North of 57.3 • N and some crossing at the Bight Fracture Zone (56-57 • N). This is coherent with the results from Petit et al (2018), which observed that water at this depth (their layer 3) was more likely to cross the ridge North of 56 • N. This southwestward flow is present in our simulations, with too intense velocity amplitudes in NATL, but realistic amplitudes at higher resolution in POLGYR. In both cases, we clearly see the flow crossing the ridge north of 56 • N.…”
Section: Mean Circulationsupporting
confidence: 91%
“…At 1000-m depth, Argo floats reveal a continuous current following the Eastern RR flank until reaching the CGFZ, with some of the flow crossing the ridge North of 57.3 • N and some crossing at the Bight Fracture Zone (56-57 • N). This is coherent with the results from Petit et al (2018), which observed that water at this depth (their layer 3) was more likely to cross the ridge North of 56 • N. This southwestward flow is present in our simulations, with too intense velocity amplitudes in NATL, but realistic amplitudes at higher resolution in POLGYR. In both cases, we clearly see the flow crossing the ridge north of 56 • N.…”
Section: Mean Circulationsupporting
confidence: 91%
“…Intermediate Water (IW) is a low‐oxygenated water mass observed in the upper 1,000 m of the water column and originating from the eastern subpolar gyre (Harvey & Arhan, ; van Aken & de Boer, ). It was observed during the RREX2015 cruise along the Reykjanes Ridge between 27.52 σ 0 and 27.71 σ 0 (Petit et al, ). At this density range, IW differs from the other water masses by having an oxygen concentration lower than 272 μmol/kg (Petit et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed during the RREX2015 cruise along the Reykjanes Ridge between 27.52 σ 0 and 27.71 σ 0 (Petit et al, ). At this density range, IW differs from the other water masses by having an oxygen concentration lower than 272 μmol/kg (Petit et al, ). IW was sampled at the CGFZ by the deep floats launched during RREX2015 and RREX2017 (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our compilation of microstructure data (Figure a) includes field campaigns described and analyzed by Waterhouse et al () as well as data from eight additional projects: INDOMIX (Bouruet‐Aubertot et al, ); OUTPACE (Bouruet‐Aubertot et al, ); three cruises over the Izu‐Ogasawara ridge, hereafter referred to as IZU (Hibiya et al, ); DoMORE (Thurnherr et al, ); RidgeMix (Vic et al, ); OVIDE (Ferron et al, ); RREX (Petit et al, ); and PROVOLO (Fer et al, ). The compilation encompasses a total of 19 campaigns cumulating 1,171 microstructure profiles.…”
Section: Comparison To Microstructure and Finestructure Observationsmentioning
confidence: 99%